The Nine Numbers of the Cosmos. - Rowan-Robinson, Michael (OUP Oxford, 1999)
How old is the universe? How far away are the galaxies and how fast are they travelling away from us? What is dark matter and why do astronomers think it pervades the universe? How heavy is the vacuum? How do galaxies form?Michael Rowan-Robinson answers these and many more questions in a highly original and intriguing way. He encapsulates our current knowledge (both what we do and don't know) of the origin and the nature of the universe into nine numbers. These cosmic numbers appear to be independent characteristics of our universe and include its age, the Hubble constant (a measure of its rat.